2011
DOI: 10.15835/nbha3926333
|View full text |Cite
|
Sign up to set email alerts
|

Several Fruit Characteristics of Rosa sp. Genotypes from the Northeastern Region of Romania

Abstract: There is great evidence regarding the beneficial influence of rose hips on human and animal health. In this respect, fruits of native populations of Rosa spp. collected from the northeastern part of Romania (400-1060 m altitude) were assayed for nutritional and some morphological properties, in order to select the best genotypes. The results show a great quantitative variability of analyzed genotypes, regarding dimensions and biochemical indicators as follow: ascorbic acid: 866.91 mg/100 g fw (R. rubiginosa), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
4
19
0
1
Order By: Relevance
“…On the other hand, the high levels of total sugars in dog rose can be ascribed to high levels of glucose and fructose. Different authors also reported high levels of total analyzed sugars in different Rosa species (Rosu and others 2011). The lowest levels of total sugars in our study were quantified in white gooseberry fruit (185.9 mmol/kg), where a very low sugars/acids ratio was measured (1.57).…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, the high levels of total sugars in dog rose can be ascribed to high levels of glucose and fructose. Different authors also reported high levels of total analyzed sugars in different Rosa species (Rosu and others 2011). The lowest levels of total sugars in our study were quantified in white gooseberry fruit (185.9 mmol/kg), where a very low sugars/acids ratio was measured (1.57).…”
Section: Resultsmentioning
confidence: 93%
“…Also, Novajan et al [27] reported that the ascorbic acid amount found in rose hip varied between 211–417.5 mg/100 g. fresh pulp, which is in agreement with our results. Other studies reported higher values of ascorbic acid, for example, Jablanska-Rys et al [28] (1252 mg/100 g fresh pulp), Rosu et al [29] (643 mg/100g fresh pulp), or lower amounts of vitamin C between 40–47 mg/100 g fresh pulp [30,31]. …”
Section: Resultsmentioning
confidence: 99%
“…The uses of Rose Hip scientifically reported so far are as functional food, antioxidant, osteoarthritis care, antiinflammatory, antidiabetic, cardioprotective, antimicrobial, immunomodulatory, gastroprotective and dermatological applications [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%